Predictors of In-Hospital Ambulatory Status Following Low-Energy Hip Fracture Surgery. (31st January 2019) - Villa, Jordan C.; Koressel, Joseph; van der List, Jelle P.; Cohn, Matthew; Wellman, David S.; Lorich, Dean G.; Lane, Joseph M.
Introduction: Twenty-five percent to seventy-five percent of independent patients do not walk independently after hip fracture (HF), and many patients experience functional loss. Early rehabilitation of functional status is associated with better long-term outcomes; however, predictors of early ambulation after HF have not been well described. Purposes: To assess the impact of perioperative and patient-specific variables on in-hospital ambulatory status following low-energy HF surgery. Methods: This is a retrospective analysis of 463 geriatric patients who required HF surgery at a metropolitan level-1 trauma center. The outcomes were time to transfer (out of bed to chair) and time to walk. Results: Three hundred ninety-two (84.7%) patients were able to transfer after surgery with a median time of 43.8 hours (quartile range: 24.7-53.69 hours), while 244 (52.7%) patients were able to walk with a median time of 50.86 hours (quartile range: 40.72-74.56 hours). Preinjury ambulators with aids (hazard ratio [HR]: 0.70, confidence interval [CI]: 0.50-0.99), age >80 years (HR: 0.66, CI: 0.52-0.84), peptic ulcer disease (HR: 0.57, CI: 0.57-0.82), depression (HR: 0.66, CI: 0.49- 0.89), time to surgery >24 hours (HR: 0.77, CI: 0.61-0.98), and surgery on Friday (HR: 0.73, CI: 0.56-0.95) were associated with delayed time to transfer. Delayed time to walk was observed in patients over 80 years old (HR: 0.74, CI: 0.56-0.98), females (HR: 0.67, CI: 0.48-0.94), peptic ulcer disease (HR: 0.23, CI: 0.84-0.66), and depression (HR: 0.51, CI: 0.33-0.77). Conclusions: Operative predictors of delayed time to transfer were surgery on Friday and time to surgery >24 hours after admission. Depression is associated with delayed time to transfer and time to walk. These data suggest that is important to perform surgeries within 24 hours of admission identify deficiencies in care during the weekends, and create rehabilitation programs specific for patient with depression. Improving functional rehabilitation after surgery may facilitate faster patient discharge, decrease inpatient care costs, and better long-term functional outcomes.